A unified framework for CBDC design: remuneration, collateral haircuts and quantity constraints - Katrin Assenmacher-Wesche; Aleksander Berentsen; Claus Brand; Nora Lamersdorf (European Central Bank (ECB), 2021)
We study the macroeconomic effects of central bank digital currency (CBDC) in a dynamic general equilibrium model. Timing and information frictions create a need for inside (bank deposits) and outside money (CBDC) to finance production. To steer the quantity of CBDC, the central bank can set the lending and deposit rates for CBDC as well as collateral and quantity requirements. Less restrictive provision of CBDC reduces bank deposits. A positive interest spread on CBDC or stricter collateral or quantity constraints reduce welfare but can contain bank disintermediation, especially if the elasticity of substitution between bank deposits and CBDC is small.
Keywords: E58; E41; E42; E51; E52; 330; Central bank digital currency; monetary policy; search and matching